Translating evidence to practice in the health professions: a randomized trial of Twitter vs Facebook. (29th June 2016) - Tunnecliff, Jacqueline; Weiner, John; Gaida, James E; Keating, Jennifer L; Morgan, Prue; Ilic, Dragan; Clearihan, Lyn; Davies, David; Sadasivan, Sivalal; Mohanty, Patitapaban; Ganesh, Shankar; Reynolds, John; et al.
Abstract : Objective: Our objective was to compare the change in research informed knowledge of health professionals and their intended practice following exposure to research information delivered by either Twitter or Facebook. Methods: This open label comparative design study randomized health professional clinicians to receive "practice points" on tendinopathy management via Twitter or Facebook. Evaluated outcomes included knowledge change and self-reported changes to clinical practice. Results: Four hundred and ninety-four participants were randomized to 1 of 2 groups and 317 responders analyzed. Both groups demonstrated improvements in knowledge and reported changes to clinical practice. There was no statistical difference between groups for the outcomes of knowledge change (P = .728), changes to clinical practice (P = .11) or the increased use of research information (P = .89). Practice points were shared more by the Twitter group (P < .001); attrition was lower in the Facebook group (P < .001). Conclusion: Research information delivered by either Twitter or Facebook can improve clinician knowledge and promote behavior change. No differences in these outcomes were observed between the Twitter and Facebook groups. Brief social media posts are as effective as longer posts for improving knowledge and promoting behavior change. Twitter may be more useful in publicizing information and Facebook for encouraging course completion.